Safety Measures and Risk Analysis for Outdoor Recreation Technicians and Practitioners: A Systematic Review. Sustainability - Mata, C (2022)
There is no expectation to suppress all accidents in the outdoor recreation sector; nevertheless, it is expected that all possible safety measures are taken in order to minimize the risk of accidents. The objective of this study was to systematize the knowledge regarding recommended and used safety measures and risk assessments for technicians and outdoor recreation practitioners. We conducted a systematic review on PubMed, BVS, SciELO, Science Direct, ABI/INFORM, Spinger, Web of Knowledge, and Esmerald full text databases, up to February 2021. The eligible criteria followed the PICOS strategy; the included risk assessment studies on outdoor recreation (according to its definition) had methodological quality, were indexed, and peer reviewed. Ten studies, from ten countries, fulfilled these specifications, which focused on different approaches. Five studies focused on risk perception, four studies focused on safety practices, injuries, and risk assessment; three studies addressed safe behaviors; two studies addressed equipment- and risk matrix-related themes. We concluded that there was a concern for this topic, and the 28 mentioned measures could provide important information regarding health and prevention. These measures could be used to develop safety strategies and risk reduction, aimed at reducing accidents in outdoor recreation activities. In order to evaluate the pertinence and importance of the mentioned measures, namely risk perception, safe practices, sport injuries, risk analysis, safe behaviors, as well as equipment and risk assessment matrices, further investigation is needed using experimental or observational designs. These strategies and procedures can contribute to enhanced interventions by technicians with higher security and quality, and therefore, improved well-being and satisfaction of practitioners.